Design and Implementation of Flappy Chick Game: A Study on Game Development Using Scratch 3 - Leny, Nurmaida; Perenggky, Perenggky; Anastasya, Anastasya (Gameology and Multimedia Expert, 2024)
In the current information era, technological advancements continue to increase in line with the progress of science and innovation in various sectors, including multimedia applications. One rapidly growing sector is the use of smartphones, which now serve not only as communication tools but also as entertainment platforms, particularly for gaming. Flappy Chick is a game where a chick must jump through pillars to collect points and avoid hitting the pillars to avoid losing. This game is designed as entertainment that can be enjoyed by all age groups. Developed using the Scratch 3 application, this game offers a simple yet enjoyable gameplay experience.